The influence of club football on children's daily physical activity. (3rd March 2016) - Nielsen, Glen; Bugge, Anna; Andersen, Lars Bo
Abstract : Studies on the effects of organized club sports on children's total amount of physical activity (PA) show varying results. This may be partly due to different sports having different activity levels, but also different possibilities for being played outside club settings. This study investigates how playing football as a club sport is associated to the total amount of daily PA among children and how increased school recess activity impacts on this. Using accelerometers, the average daily amount of children's PA as well the activity levels in specific contexts, such as during club-sports and school recess, was measured on a sample of 518 Danish children aged 9–10. The study found that children playing club football had higher total daily amounts of PA than both children taking part in other club-sports and children not taking part in club-sports at all. About half of the difference in total PA could be explained by higher activity levels during school recess. The association between club football and total PA, and the mediating effect of school recess PA, can be interpreted as the result of two main factors: the high activity levels during club football, and that Danish school grounds have football facilities which allow able and interested children to play football for many hours each week during school recess. On a more general level, the results indicate that the influence leisure-time club sport participation has on PA may differ due to how well the sport can be transferred to and played in other daily contexts for children's self-organized PA, such as school recess.